Who Is to Blame?: Content Analysis of Blogs about the Act of Terrorism at Domodedovo Airport. Issue 2 (3rd March 2016) - Gavrilov, K.A.; Tolmach, A.D.
Abstract : We present the results of a content analysis of communications related to the act of terrorism at Domodedovo airport. They show that mass media plays a significant role as a source of factual, undigested information. The theoretical value of the results is that they show a significant number of cases where an actor is accused with no reference to his actions or nonactions. The range of types of complicity in terrorist activity was substantial.